Cyclization of uridine monophosphate by diethyl pyrocarbonate. - Solymosy, F (1975)
Reaction between diethyl pyrocarbonate and uridine 2'-phosphate or uridine 3'-phosphate leads to the formation in high yields of uridine 2':3'-cyclic phosphate. This reaction product was identified in experiments involving (a) ultraviolet spectrophotometry, (b) paper chromatography, (c) high voltage paper electrophoresis at both pH 3.5 and 7.4, (d) acid hydrolysis, and (e) digestion with pancreatic ribonuclease.